Designing a knowledge management system for Naval Materials Failures - Melanitis Nikolaos (EDP Sciences, 2021)
NAVMAT Research project attempts an interdisciplinary approach by integrating Materials Engineering and Informatics under a platform of Knowledge Management. Failure analysis expands into forensics engineering for it aims not only to identify individual and symptomatic reasons of failure but to assess and understand repetitive failure patterns, which could be related to underlying material faults, design mistakes or maintenance omissions. NAVMAT approach utilizes a focused common-cause failure methodology for the naval and marine environment, to begin with. It will eventually support decision making through appropriate Artificial Intelligence and Natural Language Processing methods. The presented work describes the design of a knowledge based system dedicated to effective recording, efficient indexing, easy and accurate retrieval of information, history of maintenance and secure operation concerning failure incidents of marine materials, components and systems in a fleet organisation. Based on materials failure ontology, utilising artificial intelligence algorithms and modern approaches in data handling, NAVMAT aims at the optimisation of naval materials failure management and the support of decision making in Maintenance and Repair Operations (MRO), materials supplies and staff training.